MIGRATION PROBLEMS IN SOCIO-POLITICAL LIFE OF KABARDINO-BALKARIA AT THE END OF THE 20TH – EARLY 21ST CENTURY - A. V. KUSHKHABIEV (Кавказология)
The article presents an analysis of migration problems in their interconnection with the socio-political situation in Kabardino-Balkaria at the end of the 20th and early 21st century. It is demonstrated that intensified in the mid-1980s. the influx of migrants from Transcaucasia and Central Asia to Kabardino-Balkaria exacerbated a number of problems in the republic: housing, land, unemployment, rising crime rates, and others. Serious problems arose in Kabardino-Balkaria in connection with the stay of a significant number (over 80 thousand people) of refugees from the Chechen Republic in the mid-1990s. – the beginning of the XXI century. A regular and massive influx of Meskhetian Turks into the KBR, which began in the second half of the 20th century and continues in our days, caused a number of serious problems and had an impact on the demographic, ethno-cultural, socio-economic and delinquency situation in the republic. Their number in Kabardino-Balkaria increased from several families in 1964 to more than 20 thousand people at the present time. At the same time, there is an outflow of indigenous youth from the KBR that leads to a change in the ethnic and socio-professional composition of the population. In the areas of the Meskhetian Turks’ compact settlement the competition in the labor market is aggravated and the local, mostly Russian-speaking population is driven out the agricultural sector and from the sphere of trade. After appeals from Kabardian public organizations to the government bodies of Kabardino-Balkaria, they adopted regulatory legal acts restricting registration of migrants in the republic. The implementation of these acts to a certain extent limited the influx of migrants, but it was not possible to stop the migration flows to the republic. Illegal migrants used various workarounds. In the following years, the regulatory acts of the state authorities of the KBR to limit the registration of migrants on the territory of the KBR were terminated due to the harmonization of the regulatory acts of the republic in accordance with federal legislation.